Overcoming Alignment Problem in Non-Identical Mathematical Support Visual Cryptography Schemes - Ari Moesriami Barmawi; Widhian Bramantya (Journal of ICT Research and Applications, 2018)
An important problem in visual cryptography is the alignment problem. Although Liu, et al. have proposed a method for aligning the shares, there is still a problem with the non-identical mathematical support visual cryptography schemes. For overcoming this problem, the Three-Orthogonal-Point (3OP) method is proposed in this paper. Based on the experimental result it was proven that it can overcome the alignment problem, while the time complexity for aligning the shares is decreased significantly from O((mÃ—A)2) to O(mÃ—AI), for AI < A. The security is maintained, since an attacker cannot obtain any information related to the secret image.